The ability of platform businesses to create employment through shared value principles - Primo, Lauren (My University, 2022)
Over the past 10 years, the world has seen a rapid increase in the number of platform businesses which have been developed. These platform businesses have made a huge impact on the concept of traditional business and the principles which guide engagement, creating new methods, new markets and new ways of doing business. Platform businesses and technology based organisations occupy 7 of the top 10 spots of the global stock exchange market which is a radical shift from the traditional businesses known to occupy those space for decades. As a result of the drastic change in the business landscape, jobs and the nature of employment has also been greatly impacted. Employment, as it was once known, was being employed by one organisation for many years. The organisation would be the sole employer to the employee and the only means to an income for the employee. Employment today, has become more of an entrepreneurial venture, where an individual can offer their services to various companies simultaneously for short periods of time. This change in the nature of employment as a result in the rise of platform business has led to the question of whether platform business have the ability to create employment through shared value principles. The concept of shared value is a new concept developed by Michael Porter and Mark Kramer in 2006. The concepts’ aim was to change organisations approach towards Corporate Social Responsibility (CRS) due to its unsustainable nature as well as change the perception of capitalism that seeks to exploit society for profit. Porter and Kramer believed that organisations would be able to assist in the eradication of social and environmental challenges by encompassing these challenges into their strategic business objectives. The concept ultimately is for organisations to encompass social and environmental challenges into their strategic business objectives while simultaneously making a profit. The study depicts the potential for platform businesses to encompass shared value principles due to their ability to provide opportunities to society as actors on the platform business. As actors individuals would take on the entrepreneurial approach to employment in order to generate an income from the platform. A qualitative approach consisting of eight open-ended interviews were conducted amongst platform business owners and managers. All participants were based in South Africa
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Platform businesses; Shared value principles; UCTD; SDG-8: Decent work and economic growth